68 THE EFFECT OF ACIDOSIS AND HYPERKALEMIA ON THE IKr BLOCKING ACTION OF ANTIARRHYTHMIC DRUGS. (1st March 2006) - Lin, C.; Ke, X.; Cvetanovic, I.; Ranade, V.; Somberg, J. C.
Abstract : Regional myocardial acidosis resulting from the impaired coronary blood flow has been observed in both animal models and in man. The ischemic myocardium also releases potassium into the extracellular space, which can cause regional hyperkalemia. Antiarrhythmic agents are frequently prescribed for patients with ischemic heart disease and regional changes in pH and potassium may alter the effect of these agents. In this study, we evaluated the effect of extracellular acidosis and hyperkalemia on the action of IKr blocking antiarrhythmic drug-quinidine (Q). The IKr channel was studied at room temperature by employing human-ether-a-go-go-related gene (HERG) expressed in Xenopus oocytes and two-electrode voltage clamp technique was employed for recording. The pH of the recording bath solution was adjusted with NaOH to 6.8 or 7.4 and the recording bath solutions contained either 5 or 7.5 mmol/L KCl (5 or 7.5 K). The recording solution with 5 K, pH 7.4 represented the normal condition and 7.5 K, pH 6.8 represented acidic and hyperkalemic conditions. Q 3, 10, and 30 μM when applied at 5 K, pH 7.4 inhibited current by 17 ± 3, 39 ± 3, and 63 ± 4%. The percentage current block by Q at 7.5 K, pH 7.4 was similar to current block at 5 K, pH 7.4. Q at 7.5 K, pH 7.4 decreased HERG current by 18 ± 1, 42 ± 3, and 65 x3%. But if Q was applied at 5 K, pH 6.8, the HERG inhibitory effect of Q was decreased, and 3, 10, and 30 μM Q produced 8 ± 2, 24 ± 3, and 50 ± 4% current block. Q 3, 10, 30 μM administered in acidic and hyperkalemic condition (7.5 K, pH 6.8) caused 13 ± 2, 25 ± 2, and 47 ± 2% current inhibition, which was similar to the inhibitory effect of Q at 5 K, pH 6.8. There was a significant difference in current block by Q between 5 K, pH 7.4 and 5 K, pH 6.8, and there was also a significant difference in current inhibition by Q between 5 K, pH 7.4 and 7.5 K, pH 6.8 ( p < .05). Our data suggest that extracellular acidosis (pH 6.8) attenuates the HERG inhibitory effect of Q, and when extracellular acidosis is combined with hyperkalemia (7.5 K), the effect on IKr inhibition is similar to acidosis alone. The attenuated effect of Q at low pH may cause heterogeneity of repolarization between ischemic and normal regions, and this may set the stage for reentrant arrhythmias, contributing to Q's proarrhythmic toxicity.